Nurse-led intervention in the management of patients with cardiovascular diseases: a brief literature review - Xiaoqin Qiu (BMC, 2024)
Abstract Coronary artery disease (CAD) is one among the major causes of mortality in patients all around the globe. It has been reported by the World Health Organization (WHO) that approximately 80% of cardiovascular diseases could be prevented through lifestyle modifications. Management of CAD involves the prevention and control of cardiovascular risk factors, invasive and non-invasive treatments including coronary revascularizations, adherence to proper medications and regular outpatient follow-ups. Nurse-led clinics were intended to mainly provide supportive, educational, preventive measures and psychological support to the patients, which were completely different from therapeutic clinics. Our review focuses on the involvement and implication of nurses in the primary and secondary prevention and management of cardiovascular diseases. Nurses have a vital role in Interventional cardiology. They also have major roles during the management of cardiac complications including congestive heart failure, atrial fibrillation and heart transplantation. Today, the implementation of a nurse-led tele-consultation strategy is also gaining positive views. Therefore, a nurse-led intervention for the management of patients with cardiovascular diseases should be implemented in clinical practice. Based on advances in therapy, more research should be carried out to further investigate the effect of nurse-led clinics during the long-term treatment and management of patients with cardiovascular diseases.